Fighting for public water: the first successful European Citizens’ Initiative, “Water and Sanitation are a Human Right” - Bieler, Andreas (2017)
Between May 2012 and September 2013 the European Citizens’ Initiative (ECI) ‘Water and Sanitation are a Human Right’ successfully collected close to 1.9 million signatures across the European Union (EU), forcing the Commission into an official position on the role of water in the EU and wider world. Based on a historical materialist approach to social movement struggles, the purpose of this article is threefold. First it will analyse the reasons for why the ECI, initiated and co-ordinated by the European Federation of Public Service Unions (EPSU), was so successful. Second, the article will assess the impact of the ECI on EU policy-making. Finally, the article will reflect on the wider lessons to be learned for the struggle against neo-liberal restructuring. It will be argued that a combined focus on the commons as well as new forms of participatory democracy may provide the basis for a broader transformative project.